Color psychology in advertising / Puteri Adlin Afina Azam Fitri - Azam Fitri, Puteri Adlin Afina (Faculty of Art and Design, 2020)
This current modern era. Advertising has several types of techniques used to attract consumers to a product or service. The most commonly used techniques are those involving human psychology that gives a touch to the heart but gives high impact. According to Orana Velarde (Visme.com. 2016), marketing a product or service by touching emotions or memories related to sentimental issues to consumers can remind personal information about them when associating with the product or service, which shares about importance and benefits of the product or service. Successful advertisements can appeal to consumers and create a sense of normalcy and encourage potential users to be attracted to them so that they buy or create something that is shared within the advertisement Most advertisements and campaigns of a product or service use one of several popular and effective techniques, and some of them are techniques that use human psychological learning (Tara Kimball,2018), In addition, some advertisements use direct sales techniques that inform consumers and potential consumers directly about the products or services offered. That way, users will get information directly and consistently with a user-friendly understanding